Vaccine Adherence and Behavioral Changes of Adults Regarding Prevention of COVID-19: A Community Survey Using the Theory of Planned Behavior - Haque, Md. Nazmul; Alam, Muhammed Ashraful; Saha, Shuvashis; Panthumas, Suphawadee; Clara, Afrin Ahmed; Sharif, Md. Parvez Iqbal (Journal of Population and Social Studies [JPSS], 2023)
Considering the current context of the coronavirus 2019 (COVID-19) pandemic, people should equally comply with both vaccines and non-therapeutic health protective behaviors. This study investigated public adherence to vaccination, behavioral changes against COVID-19, and their determinants in Bangladesh during the pandemic. The study was conducted during May and June 2022 among 940 Bangladeshi adults selected by multi-stage sampling, and data were collected through face-to-face interviews using questionnaires. Significant determinants and their relationships were described through hierarchical regression and structural equation modeling (SEM) based on the theory of planned behavior (TPB). Nearly half of the subjects (48.2%) showed poor vaccine adherence and COVID-19 prevention practices. During the pandemic crisis, the majority of the respondents (86.7%) used face masks, but only 12.7% of the respondents used them regularly. Less than half (44.9%) received COVID-19 vaccines regularly. Along with some sociodemographic factors, knowledge (p < .001), attitude (p < .01), and intention (p < .001) regarding COVID-19 prevention were significant in predicting vaccine adherence and healthy practices in a hierarchical regression. Self-control was highly significant in SEM, showing the highest effect (p < .001). Policies based on the TPB model could be adopted to improve preventive behaviors against COVID-19.